Gender Differences in Internet Addiction and Tendency to Express Emotions - Oktuğ, Bige Zeynep (My University, 2012)
Social media applications become integral parts of daily life. People begin to live their emotions through these applications. Studies show that the main reason of using social networks is making social relations easier. But because of the excessive use of internet, the person can fall short off the real world, and that can give way to isolation and loneliness. Trying to decrease these emotions through establishing relations in virtual world, the person can be deprived of the benefits of face to face communication. The aim of this study is to analyze whether a gender-based difference exists between internet addiction and the tendency towards expressing emotions; to examine the relation between internet addiction and the ability to express emotions and to determine whether the degree for expression of emotions is a meaningful predictor of internet addiction. The results show that internet addiction among women is higher than among men, but there is no difference between the genders with respect to the degrees for expression of emotions. According to the results, eight percent of internet addiction can be explained by emotion expression skills. In future research, social and psychological factors may also be analyzed for aspects of their effect on the relation between internet addiction and the expression of emotions.